Peran UNAIDS Dalam Menangani Masalah HIV/AIDS Terhadap Perempuan di Afrika Selatan Pada Tahun 2011-2015 - Apsari, Ni Made Listu Ayu Belia; Priadarsini, Ni Wayan Rainy; Parameswari, A.A. Ayu Intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2019)
ABSTRACT   This research is conducted with qualitative research method to compile how UNAIDS as an international organization tackling the problem of HIV/AIDS that effect women in South Africa. South Africa has the most people with HIV/AIDS in the world. The number of women who suffers from HIV/AIDS is higher compared to the number of male who is infected with HIV/AIDS. Women also suffers from the great impact of HIV/AIDS. UNAIDS as an international organization which works on HIV/AIDS field also highlighted the problem of HIV/AIDS against women. UNAIDS in its role as an actor has recommended a lot of policies to South Africa, which South Africa put the policies into action. Those policies has successfully make the HIV/AIDS prevalence number on women decreased.                                                 Keywords: UNAIDS, International Organization, HIV/AIDS